Large-Scale Vole Population Synchrony in Central Europe Revealed by Kestrel Breeding Performance - Fay, Rémi; Michler, Stephanie; Laesser, Jacques; Jeanmonod, Jacques; Schaub, Michael (Frontiers in Ecology and Evolution, 2020)
Rodents are classical model species to investigate spatial synchrony in population fluctuation. Yet, previous studies have been strongly biased geographically toward high latitude (boreal ecosystem) and limited in their spatial scale, i.e. few sampling sites separated by a few tens of kilometers. Both aspects currently limit our understanding of rodent population dynamics across space. In this study we investigate vole population synchrony at a large spatial scale in central Europe. We used long-term breeding success of a vole-eating raptor specialist, the European kestrel, as an indicator of vole abundance. We first demonstrate that the productivity of kestrels is highly dependent on the availability of voles and as such is a good proxy of vole abundance. Secondly, we assessed the spatial synchrony of kestrel productivity and its scaling. We found that kestrel productivity fluctuated synchronously at a large spatial scale, up to a distance of 300 km. This result suggests that vole populations in central Europe varied in synchrony at large spatial scales, similarly as in northern latitudes. The most likely mechanism resulting in such large scale synchrony of vole populations is synchronized density-independent environmental conditions.